Modelling the potential spread of Clade Ib MPXV in Asian cities - Kiesha Prem; Rayner Kay Jin Tan; Akira Endo; Gregory Gan; Keisuke Ejima; Jue Tao Lim; Borame L Dickens; Shihui Jin (BMJ Public Health, 2025)
Background The ongoing 2023–2024 mpox outbreak in several African countries, driven by the novel Clade Ib strain, has resulted in imported cases being reported in Sweden, Thailand and India. The potential high transmissibility of this new strain and shifts in transmission modes may make territories in Asia, which were minimally affected by previous mpox waves, susceptible to community-wide transmission following importation. While this highlights the importance of early preparedness, current knowledge of the virus’s transmission dynamics remains too limited to effectively inform policymaking and resource planning.Methods A compartmental model was constructed to characterise potential mpox transmission dynamics. Importation-triggered outbreaks were simulated in 37 Asian cities under scenarios with one, three and five initial local infections. The impacts of various non-pharmaceutical interventions (NPIs), including isolation and quarantine, were projected and compared.Findings Our simulations revealed substantial disparities in outbreak sizes among the 37 Asian cities with large-scale outbreaks expected in territories with a high proportion of sexually active individuals at risk or low immunity from smallpox vaccination. Total case counts in 1 year following initial local infections would increase linearly with initial infection size. In the scenario with three initial local infections, up to 340 cases per million residents were expected without interventions. Isolation for diagnosed cases was projected to lower the outbreak size by 43.8% (IQR: 42.7–44.5%), 67.8% (IQR: 66.5–68.9%), 80.8% (IQR: 79.5–82.0%) and 88.0% (IQR: 86.8–89.1%) when it reduced interpersonal contacts by 25%, 50%, 75% and 100%, respectively. Quarantining close contacts would contribute to a further decrease in cases of up to 22 percentage points over 1 year.Interpretation A potential mpox outbreak in an Asian setting could be alleviated through strong surveillance and a timely response from stakeholders. NPIs are recommended for outbreak management due to their demonstrated effectiveness and practicability.